Derive the equation for the deflected shape of theDerive the equation for the deflected shape of the beam neutral axis y(x) for the Beam loaded as shown below. Your answer is an equation Y(x, P, a, E, l, L). What is the value of the vertical displacement at the free end of the beam? E = Modulus of Elasticity I = Moment of inertia P = Value of applied point load Pa = value of the applied moment L = beam length Show transcribed image text Derive the equation for the deflected shape of the beam neutral axis y(x) for the Beam loaded as shown below. Your answer is an equation Y(x, P, a, E, l, L). What is the value of the vertical displacement at the free end of the beam? E = Modulus of Elasticity I = Moment of inertia P = Value of applied point load Pa = value of the applied moment L = beam length